Effect of urea supplementation to urea molasses mineral block (UMMB) lick on nutrient utilization and rumen fermentation pattern in crossbred cattle - TOPPO, SAROJ; MEHRA, U R; DASS, R S (The Indian Journal of Animal Sciences, 2013)
The effect of incremental urea supplementation on intake of urea-molasscs mineral blocks (UMMB), nutrient utilization and rumen ferntentation was investigated on 16 adult crossbred cattle. They were divided into 4 equal groups following u completcly randomized design. Animals were offered wheat straw and UMMB lick ad lib. and crushed maize grains to meet out the energy requirements. In addition to this, animals in groups 1 to 4 were offered urea @ 0, 15,30 and 45 g/ animal a day, respectively, A metabolism trial of 6 days duration was conducted, Results revealed that intake and digestibility of all the nutrients were alike except that CP intake was significantly (P